2007
DOI: 10.1074/jbc.m611841200
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124a Regulates Foxa2 Expression and Intracellular Signaling in Pancreatic β-Cell Lines

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs that have been implicated in fine-tuning gene regulation, although the precise roles of many are still unknown. Pancreatic development is characterized by the complex sequential expression of a gamut of transcription factors. We have performed miRNA expression profiling at two key stages of mouse embryonic pancreas development, e14.5 and e18.5. miR-124a2 expression was strikingly increased at e18.5 compared with e14.5, suggesting a possible role in differentiated ␤-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
311
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(323 citation statements)
references
References 57 publications
8
311
2
2
Order By: Relevance
“…Previous studies have reported mir-375, mir-9, mir-124a and mir-96 to play a role in regulation of insulin secretion in rodent pancreatic beta cell lines MIN6, INS-IE and MIN6 B1 cells [1][2][3][4]; however, in this study, mir-375, mir-9, mir-124a and mir-96…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Previous studies have reported mir-375, mir-9, mir-124a and mir-96 to play a role in regulation of insulin secretion in rodent pancreatic beta cell lines MIN6, INS-IE and MIN6 B1 cells [1][2][3][4]; however, in this study, mir-375, mir-9, mir-124a and mir-96…”
Section: Discussioncontrasting
confidence: 76%
“…Much is known of the mechanisms of GSIS and the proteins involved therein; however, the specific regulation of exocytosis-related proteins remains less well understood. A small number of miRNAs have been shown to play a role in regulation of components of the insulin secretory pathway [1][2][3]. This study aimed to investigate the feasibility of identifying other miRNAs involved in the process of GSIS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been shown to regulate the Caenorhabditis elegans developmental timing (6,36), as well as the embryonic and post embryonic differentiation in rodents (37,38) and in human beings (39)(40)(41). MiRNAs have been involved in physiological processes, such as insulin regulation (42,43), lipid metabolism (44) and synaptic activity, (45).…”
Section: Significance Of Microrna Profilingmentioning
confidence: 99%